2020
DOI: 10.1038/s41598-020-66447-2
|View full text |Cite|
|
Sign up to set email alerts
|

Splice-specific deficiency of the PTSD-associated gene PAC1 leads to a paradoxical age-dependent stress behavior

Abstract: The pituitary adenylate cyclase-activating polypeptide receptor (PAC1, also known as ADCYAP1R1) is associated with post-traumatic stress disorder and modulation of stress response in general. Alternative splicing of PAC1 results in multiple gene products, which differ in their mode of signalling and tissue distribution. However, the roles of distinct splice variants in the regulation of stress behavior is poorly understood. Alternative splicing of a short exon, which is known as the "hop cassette", occurs duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Single guide RNA (sgRNA) design and synthesis was performed, as previously described 32 with slight modifications. Briefly, gRNA was designed using CHOP-CHOP, 33 transcribed in vitro using MEGAshortscript T7 kit (Life Technologies, Carlsbad, CA), and purified using a miRNeasy kit (Qiagen, Germantown, MD).…”
Section: Design Of Crispr Target Sites and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Single guide RNA (sgRNA) design and synthesis was performed, as previously described 32 with slight modifications. Briefly, gRNA was designed using CHOP-CHOP, 33 transcribed in vitro using MEGAshortscript T7 kit (Life Technologies, Carlsbad, CA), and purified using a miRNeasy kit (Qiagen, Germantown, MD).…”
Section: Design Of Crispr Target Sites and Synthesismentioning
confidence: 99%
“…Microinjection to tilapia zygotes and gRNA/Cas9 heterocomplexing were performed as previously described. 26,32 Tilapia zygotes were collected immediately after natural spawning or IVF and chilled on ice to 21掳C to prolong microinjection time at the single-cell stage. In each microinjection session, zygotes were injected with a mix containing a single or two to three mixed slc45a2 gRNAs (100 pmol for each crRNA and tracrRNA; 39.72 pmol for sgRNA) mixed with rCas9 (4.4 lg) to a final volume of 9 lL.…”
Section: Microinjection Proceduresmentioning
confidence: 99%
“…Comparison of the pig ADCYAP1R1 protein sequences identified that the different transcripts corresponded to the third intercellular loop that generate differential responses to PACAP-27 [70]. Compared to normal zebrafish (Danio renio), larvae lacking the hop exon had increased anxiety-like behavior [71,72]. AD-CYAP1 is a member of the circadian entrainment pathway and considered a potential target for therapies to ameliorate drug abuse, migraine, stress-related psychopathologies and inflammatory diseases [69,[73][74][75][76][77][78].…”
Section: Transcript Isoform Characterization Of Maternal Immune Activation Effectsmentioning
confidence: 99%
“…The role of endogenous PACAP has been explored with the help of PACAP gene-deficient mice. These mice show several developmental and behavioral alterations, including altered neurobehavioral, bone, and tooth development (Farkas et al 2017;Fulop et al 2019b;Jozsa et al 2018), paradoxical age-dependent stress behavior (Biran et al 2020), and altered light responses (Riedel et al 2020). The strong neuro-and general cytoprotective role of PACAP are mainly due to its anti-apoptotic, antioxidant, and anti-inflammatory effects (Soles-Tarres et al 2020;Toth et al 2020).…”
Section: Introductionmentioning
confidence: 99%